2005
DOI: 10.1021/jf0502395
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antioxidative Effects of Alkamides, Caffeic Acid Derivatives, and Polysaccharide Fractions from Echinacea purpurea on in Vitro Oxidation of Human Low-Density Lipoproteins

Abstract: Preparations of Echinacea are widely used as alternative remedies to prevent the common cold and infections in the upper respiratory tract. After extraction, fractionation, and isolation, the antioxidant activity of three extracts, one alkamide fraction, four polysaccharide-containing fractions, and three caffeic acid derivatives from Echinacea purpurea root was evaluated by measuring their inhibition of in vitro Cu(II)-catalyzed oxidation of human low-density lipoprotein (LDL). The antioxidant activities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 32 publications
(49 reference statements)
1
99
0
1
Order By: Relevance
“…The activity of CA against herpes simplex virus has been demonstrated (Binns et al 2002). The antioxidant activity of CA was found to be comparable with that of rosmarinic acid (Dalby-Brown et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…The activity of CA against herpes simplex virus has been demonstrated (Binns et al 2002). The antioxidant activity of CA was found to be comparable with that of rosmarinic acid (Dalby-Brown et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Antioxidants are compounds that protect cells against the damaging effects of reactive oxygen species (3). Experimental studies were performed on three plants that have antioxidative properties -Ginkgo biloba, Panax ginseng, and Echinacea purpurea (4). Ginkgo biloba preparations are used in the treatment of Parkinson's and Alzheimer's diseases caused by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the effect of EPAL has only been observed for Bas. According to the results of other studies, this effect may be related to the phytochemically active constituents of EPAL (Hu and Kitts, 2000;Dalby-Brown et al, 2005;Pellati et al, 2005).…”
Section: Haematological Findingsmentioning
confidence: 74%
“…The chromatographic analysis reported 0.37% echinacoside. Echinacoside, which is responsible for the immunostimulatory action of Echinacea extracts (Hu and Kitts, 2000;Dalby-Brown et al, 2005;Pellati et al, 2005), was found to be the main caffeic acid derivative in EPAL extract. Echinacoside has frequently been studied for its antioxidant, anti-inflammatory and cicatrising activities (Speroni et al, 2002).…”
Section: Hplc Profile Of Epalmentioning
confidence: 99%